Analysis of the causes of students having a startup business in HIPMI students at PT Widyatama University - Ferdian Dwiyanto; I Solihin (Institute of Computer Science (IOCS), 2023)
Entrepreneurship is one activity that can lead to economic growth for a country. The development of business in Indonesia is currently very rapid. This study tries to find out why student members of HIPMI PT Widyatama University have startup businesses. This study uses a qualitative method with a descriptive research type. The number of samples in this study were 30 students using simple random sampling method. The data analysis technique used is descriptive statistical analysis and factor identification descriptive analysis. The results of the study show that the biggest cause that motivates students who are members of HIPMI PT Widyatama University already have their own business or business, namely wanting to earn additional income. The results of this study indicate that capital and network factors are one of the strongest causes for students to start a business when compared to social support. The results of this study are also expected to be a reference for students, especially for starting a business as one of the implementations of entrepreneurship courses.